Decoding Pure Malware : Technical Insights, Case Studies, and Mitigation Strategies - Dr. N. Kala; Premanand Narasimhan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The Pure malware family, comprising components like PureCrypter, PureLogs, and PureMiner, represents a sophisticated and growing threat to global cybersecurity. This study delves into the malware’s technical intricacies, its track record, and its alignment with frameworks like MITRE ATT&CK, CAPEC, and Palo Alto Unit 42. Through detailed case studies, we explore its impact on cloud infrastructure, virtual machines, containers, and caches. The study also proposes AI-powered mitigation strategies, digital forensics methodologies, reverse engineering practices, and proactive organizational policies to counteract such threats. Visualizations such as geofence maps, bar graphs, and timelines highlight the geographical and financial implications of Pure malware.